2015
DOI: 10.1186/s13073-015-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Many obesity-associated SNPs strongly associate with DNA methylation changes at proximal promoters and enhancers

Abstract: BackgroundThe mechanisms by which genetic variants, such as single nucleotide polymorphisms (SNPs), identified in genome-wide association studies act to influence body mass remain unknown for most of these SNPs, which continue to puzzle the scientific community. Recent evidence points to the epigenetic and chromatin states of the genome as having important roles.MethodsWe genotyped 355 healthy young individuals for 52 known obesity-associated SNPs and obtained DNA methylation levels in their blood using the Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 84 publications
6
90
0
5
Order By: Relevance
“…Early evidence demonstrated that the risk allele of FTO promotes increased methylation of sites within intron 1 of the FTO gene, as well as greater methylation of additional genes [257]. Other evidence identified 28 obesity-associated SNPs that were associated with differential methylation at 107 proximal CpG sites [258]. A recent study of Trim28 haploinsufficiency used findings from mice and humans to demonstrate the variation in obesity phenotypes that can be induced through epigenetic changes [259].…”
Section: Biological Processes Underlying Statistical Gene-environmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Early evidence demonstrated that the risk allele of FTO promotes increased methylation of sites within intron 1 of the FTO gene, as well as greater methylation of additional genes [257]. Other evidence identified 28 obesity-associated SNPs that were associated with differential methylation at 107 proximal CpG sites [258]. A recent study of Trim28 haploinsufficiency used findings from mice and humans to demonstrate the variation in obesity phenotypes that can be induced through epigenetic changes [259].…”
Section: Biological Processes Underlying Statistical Gene-environmentmentioning
confidence: 96%
“…In order to refine the search for interaction variants, statistical GEI tests could be combined with methylation quantitative trait loci (meQTL), expression quantitative trait loci (eQTL), and protein quantitative trait loci (pQTL) to focus on SNPs with a plausible biological mechanism for interaction [258]. Specifically, a joint test could be applied to (1) identify genetic variants that statistically interact with a given environmental exposure (e.g.…”
Section: Future Directions For Gene-environment Interactions and Obesitymentioning
confidence: 99%
“…There have been numerous reports of SNPs affecting the hypermethylation of proximal and trans-gene CpG islands, [2][3][4][5][6] Table 3. Allele frequencies for the non-hg19 SNP alleles that occur most frequently in the indicated data sets and that create or eliminate CpG's.…”
Section: Discussionmentioning
confidence: 99%
“…Es konnte bereits gezeigt werden, dass selbst SNPs in großer Distanz, sogar auf anderen Chromosomen, mit Veränderungen der DNA-Methylierung und damit der Regulation von Genen assoziiert sind [33]. Für Adipositas konnte ein solcher Zusammenhang mit DNA-Methylierung für 28 SNPs gezeigt werden, die ursprünglich in GWAs identifiziert wurden [34]. Die systematischen Untersuchungen des gesamten "Epigenoms" stecken momentan noch in den Anfängen.…”
Section: Abb 3 Effekte Der Vonunclassified